Attitudes towards HPV and COVID school-entry policies among adults living in Puerto Rico - Jessica N. Rivera-Rivera; Olga L. Díaz-Miranda; Diana T. Medina-Laabes; Erick Suárez; Ana P. Ortiz; Vivian Colón-López (Taylor & Francis Group, 2023)
Prior to the COVID pandemic, Puerto Rico (PR) had one of the highest Human Papillomavirus (HPV) vaccine rates in the United States. The COVID pandemic and administration of COVID vaccines might have impacted attitudes toward HPV vaccination. This study compared attitudes toward HPV and COVID vaccines with respect to school-entry policies among adults living in PR. A convenience sample of 222 adults (≥21 years old) completed an online survey from November 2021 to January 2022. Participants answered questions about HPV and COVID vaccines, attitudes toward vaccination policies for school-entry, and perceptions of sources of information. We assessed the magnitude of association between the agreement of school-entry policies for COVID and HPV vaccination by estimating the prevalence ratio (PRadjusted) with 95% Confidence Intervals (95% CI). The most trusted source of information for HPV and COVID vaccines were healthcare providers (42% and 17%, respectively) and the CDC (35% and 55%, respectively), while the least trusted were social media (40% and 39%, respectively), and friends and family (23% n = 47, and 17% n = 33, respectively). Most participants agreed that HPV (76% n = 156) and COVID vaccines (69% n = 136) should be a school-entry requirement. Agreement with school policy requiring COVID vaccination was significantly associated with agreement of school policy requiring HPV vaccination (PRadjusted:1.96; 95% CI:1.48-2.61) after controlling for potential confounders. Adults living in PR have an overall positive attitude about mandatory HPV and COVID vaccination school-entry policies, which are interrelated. Further research should elucidate the implications of the COVID pandemic on HPV vaccine attitudes and adherence rates.